1993
DOI: 10.1152/ajpcell.1993.264.6.c1577
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the red blood cell calcium pump by eosin and other fluorescein analogues

Abstract: This paper addresses the mechanism of inhibition of the plasma membrane Ca pump by fluorescein analogues and their isothiocyanate derivatives. Eosin (i.e., tetrabromofluorescein) was found to be one of the most potent reversible inhibitors of the erythrocyte Ca pump [half-maximal inhibitory concentration (IC50) < 0.2 microM]; fluorescein itself was about four orders of magnitude less potent (IC50 approximately 1,000 microM). Eosin decreased the maximum influx and thus did not compete with ATP for the Ca pump. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 22 publications
4
96
0
2
Order By: Relevance
“…Eosin, in addition to inhibiting the Na pump, also inhibits the plasma membrane Ca pump from red cells [20] and smooth muscle [35]. Interestingly, those studies found that eosin was not competitive with ATP, similar to the results presented here for the Na pump.…”
Section: Previous Worksupporting
confidence: 81%
See 3 more Smart Citations
“…Eosin, in addition to inhibiting the Na pump, also inhibits the plasma membrane Ca pump from red cells [20] and smooth muscle [35]. Interestingly, those studies found that eosin was not competitive with ATP, similar to the results presented here for the Na pump.…”
Section: Previous Worksupporting
confidence: 81%
“…Indeed, the nucleotide site binding efficiency of eosin remains an exploited tool for real-time fluorescent monitoring of nucleotide binding site conformational changes [17,18,19]. Thus, it was surprising when we observed that eosin non-competitively inhibited ATP hydrolysis and ATP-dependent 45 Ca ++ transport in the red cell plasma membrane Ca-ATPase [20]. Yet, like other P-type ATPases, FITC was an irreversible, ATP-protectable, inhibitor of PMCA, which modified the same conserved lysine residue (i.e.…”
Section: Fluorescein Inhibitionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, they can lack resolution, can be difficult to calibrate and may be toxic. BCECF also inhibits the Ca 2 + -H+ pump (Gatto & Milanick, 1993), which is an important activity-dependent acid loader in neurones (Trapp et al 1996;Schwiening, 1997).…”
Section: Department Of Physiology University Of Cambridge Downing Smentioning
confidence: 99%